2021
DOI: 10.1002/marc.202100474
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Unique Shape Transformation of Giant Polymersomes with Tubular Protrusions

Abstract: Light‐triggered unique shape transformation of calcein‐loaded giant polymersomes with tubular protrusions, which serve as a reservoir membrane area during the shape transformation, is reported here. Under irradiation at the excitation wavelength of calcein, the tubular protrusions form strings of budded vesicles and then reintegrate into the mother vesicle. The initial giant polymersomes transform to two connected spherical vesicles via two pathways to alleviate the osmotic pressure imbalance across the vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Coupled deformation is enabled through the sequential coupling of two basic deformation pathways. Besides the above-mentioned pathway, there also exist other deformation pathways, such as vesicle to micelle, rupture of the vesicle, formation of the polyhedral vesicle, etc. , These deformation pathways will not be discussed in this Account.…”
Section: Basic Deformation Of Polymer Vesiclesmentioning
confidence: 99%
“…Coupled deformation is enabled through the sequential coupling of two basic deformation pathways. Besides the above-mentioned pathway, there also exist other deformation pathways, such as vesicle to micelle, rupture of the vesicle, formation of the polyhedral vesicle, etc. , These deformation pathways will not be discussed in this Account.…”
Section: Basic Deformation Of Polymer Vesiclesmentioning
confidence: 99%
“…Copolymer components in a dilute solution aggregate, which is considered as spinodal decomposition, followed by the formation of stable droplets that gradually increase in size. As the droplets grow in size, they also reorganize into micelles 73 Light irradiation Amphiphilic block copolymer PBD-b-PEO Agarose-assisted hydration Rupture of giant vesicle 74 Light irradiation Amphiphilic block copolymer PBD-b-PEO Emulsioncentrifugation Aggregation and disassembly 75 Light irradiation Amphiphilic block copolymer and expand into semivesicles through solvent diffusion, resembling an evaporation−condensation sequence. Ultimately, the larger micelles absorb more solvent molecules, resulting in a reduction of bending energy, while simultaneous interior rearrangements of copolymer segments take place.…”
Section: Self-assemblymentioning
confidence: 99%
“…Ren and Malmstadt et al reported that giant polymersomes with tubular protrusions underwent two shape transformation pathways into two connected spherical vesicles via light triggering. 73 In the first pathway, the oblate shaped polymersomes sequentially deformed into a peanut shape, a dumbbell shape, and finally separated into two spherical polymersomes. In terms of the second one, the oblate shaped polymersome depressed inward to form an internally spherical daughter polymersome, then slowly recombined into the mother polymersome, becoming peanut-shaped, then dumbbell-shaped, and finally into two connected spherical polymersomes.…”
Section: Additive-induced Shape Transformationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the micron length scale, the deformation of poly(butadiene)‐ b ‐poly(ethylene oxide)(PB‐ b ‐PEO) GUVs with small tubular extensions resulting from an increase of osmotic pressure inside the GUVs culminated in the formation of two connected vesicles. [ 31 ] Morphological changes were also observed in rather small p‐GUVs (≈1.4 µm) produced by a microfluidic approach from a temperature sensitive triblock poly( N ‐vinylcaprolactam) 15 ‐ b ‐poly(dimethylsiloxane) 65 ‐ b ‐poly( N ‐vinylcapro‐lactam) 15 triblock copolymer (PVCL 15 ‐ b ‐PDMS65‐ b ‐PVCL 15 ). [ 248 ] At 42 °C, where PNVCL exhibits lower critical solution temperature (LCST) behavior, the collapse of PVCL blocks led to the onset of membrane buckling which facilitated the segmentation of bent membrane into multiple small vesicles.…”
Section: Harnessing the Ability For Adaptive Behaviormentioning
confidence: 99%